Examination of the Physical Activity of Amateur and Hobby E-sport Players - Sánta, János (International Journal of Engineering and Management Sciences, 2022)
With the spread of computers and the Internet, e-sports became a fast and dynamic growing sector with a significant market and economic potential. Its importance is demonstrated by the fact that its growth is now outstripping some traditional sports or other industries. E-sports users are sedentary in front of a computer during both competition and training, so their health is determined by the amount of physical activity they do when they are not in front of a computer. The primary aim of this research is to investigate the physical activity of e-sports users at different levels. In addition to this, I considered it important to investigate what games the players I interviewed compete in, how much time they spend playing and how they improve their skills. I conducted an online questionnaire survey in the University Electronic Games (UEG) online tournaments organised by the University of Debrecen. The participants in the survey fully met my criteria, as most of them were amateur or hobby e-sports players, so I obtained relevant data from their answers. Based on the participants’ responses, it can generally be said that they engage in health-enhancing physical activity. However, it should be remembered that not only the rise in popularity of e-sports, but also the increasing digitalisation of society is contributing to the rise in sedentary lifestyles. In the future, it would be important to change the way gamers exercise, which until now has been predominantly to develop their digital video game skills. Physical activity and other health-related behaviours need to be integrated into the training routines of gamers - e-sports players, so that playing sports could become a natural pastime alongside e-sports.